A Tree Story: Narratives of Paraserianthes Falcataria L. Nielsen (Falcata) Farmers - Dacanay, Lorlaine Retes (Open Science Journal, 2018)
The study narrates the plantation to industrialization processes of Falcata trees through the lens of the Falcata farmers. It recounts the: a) pre-planting story, b) planting story, c) harvest story, d) market story, and e) industry story. This is a narrative research, using post-structuralist approach, and putting forth three philosophical stances: logical positivism, narrative fidelity, and aesthetic finality. Pre-planting story progresses from the motivation of the farmers to plant and his challenges prior to planting season, soil and land preparation, and seedling choice. Planting Story is about the soil, financial matters, trees and the government support to the farming activities. Harvesting Story depends on the land area to be harvested, harvesting mode, harvesting activities and the owner’s return of his investment. Market Story encompasses the search and selection of buyers; and the projected income if the trees are sold. Industrialization Story from the hind sight of the farmers. They only presume that these trees are made into particular products; but the method of making them is unknown to the farmers. The stories of assuring and distressful outlooks of tree farmers reveal much about the Falcata tree industry. Maintaining the stand point of narration, it is revealed that marketing comes before harvesting; and thus alters the order of narrative structure and content. Keywords: Falcata trees, Farmer’s Perspectives, Narrative Research, Tree Farming, Timber Species, Philippines, Asia